Toyama City : Compact City Development - Kriss, Paul; Miki-Imoto, Haruka; Nishimaki, Hiroshi; Riku, Takashi (World Bank, Washington, DC, 2020)
This case study is showcases examples where the “G20 Principles for Quality Infrastructure Investment (QII)” have been operationalized in Japan`s urban infrastructure projects. It highlights Toyama City, which is now a global role model for compact city development and reviews the city’s difficult journey towards a compact city through the lens of Economic Efficiency and Infrastructure Governance, which are two of the six G20 Principles for QII. This case study sheds light on the importance of governance aspects such as alignment with the national policy, organizational commitment, and collaboration with the private sector. Furthermore, it illustrates how effective governance can lead to economic efficiency and some evidence of a compact city`s wider benefits. The implications are expected to benefit policymakers and practitioners in developing countries.